2006
DOI: 10.1143/jpsj.75.084801
|View full text |Cite
|
Sign up to set email alerts
|

Passive Exposure to Mobile Phones: Enhancement of Intensity by Reflection

Abstract: In a recent Letter [J. Phys. Soc. Jpn. 71, 432 (2002)], we reported a preliminary calculation and concluded that public exposure to mobile phones can be enhanced by microwave reflection in public spaces. In this paper, we confirm the significance of microwave reflection reported in our previous Letter by experimental and numerical studies. Furthermore, we show that "hot spots" often emerge in reflective areas, where the local exposure level is much higher than average. Such places include elevators, and we dis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 12 publications
0
8
0
1
Order By: Relevance
“…A study between the two cases (with and without occupant) showed that the effect of an absorber in the global distribution of microwaves is negligible compared to the order of strengthening the intensity of reflection [7].…”
Section: B the Electromagnetic Environment Been Researchedmentioning
confidence: 99%
“…A study between the two cases (with and without occupant) showed that the effect of an absorber in the global distribution of microwaves is negligible compared to the order of strengthening the intensity of reflection [7].…”
Section: B the Electromagnetic Environment Been Researchedmentioning
confidence: 99%
“…In the first problem, the passenger uses a mobile phone with no other passengers around. In this situation, passive RF exposure [4] does not exist. We have previously reported that there is a significant increase in the spatial 10-g SAR and the wholebody average SAR as compared to the free-space case [6].…”
Section: Introductionmentioning
confidence: 99%
“…The main concern is the resultant adverse health effects. The problem of human safety in enclosed environment was recent raised by Hondo et al, [3][4]. However, it should be noted here that the only scientifically established adverse health effect of RF energy in the human body is thermal and its safety limits are given based on specific absorption rates (SAR).…”
Section: Introductionmentioning
confidence: 99%
“…Human body exposure to multiple mobile phone sources inside enclosed spaces such as trains and elevators have been presented in [5,6]. The mechanisms of near-field interaction between dipoles and mobile phone models and homogeneous body models are examined in [7,8].…”
Section: Introductionmentioning
confidence: 99%